Pengaruh Kepercayaan Dan Persepsi Risiko Terhadap Keputusan Pembelian Online Shop Tokopedia - Fuji Puspa Sari; Hawignyo Hawignyo (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine the effect partially and simultaneously between Trust and Risk Perception on Online Shop Purchase Decisions of Tokopedia users in Karawang. This type of research is a quantitative research with descriptive and verification research methods. The population used in this study were users of the Tokopeia application in Karawang. The sample in this study amounted to 150 people using the Nonprobability Sampling technique. The test tool used in this research is SPSS version 25 software. The analysis model in this study uses a path analysis model. Based on the results of the study, it shows that there is a partial influence between Trust and Risk Perception of Online Shop Purchase Decisions of Tokopedia users in Karawang. The magnitude of the partial influence of Trust on Online Shop Purchase Decisions of Tokopedia users in Karawang is 17.2%, while the effect of Risk Perception on Online Shop Purchase Decisions of Tokopedia users in Karawang is 42%. Simultaneously, the effect of trust and risk perception on purchasing decisions based on the results of the study shows that the magnitude of the simultaneous influence is 59.2% and the remaining 40.8% is the influence of other variables not examined in this study. Keywords: Trust, Perceived Risk, Purchasing Decisions